Enhanced gust load recovery for the AW609 tiltrotor - Fonte, F.; Favale, M.; Rigo, A.; Quaranta, G. (My University, 2019)
The prediction of dynamic gust loads for a tiltrotor is a challenging task since it requires to take in account several components such as the flexibility of the airframe and of the rotor, their aerodynamic properties and the effect of the automated flight control systems. The characterization of the aerodynamic forces acting on the tiltrotor, in particular, can be very difficult and the direct use of unsteady aerodynamic forces from simplified panel methods can lead to a wrong definition of the dynamic properties of the rigid modes of the aircraft. A correction of the unsteady aerodynamic forces using tabulated stability derivatives can then be used to recover the proper aircraft dynamics. The use of a reduced basis for the characterization of the structural dynamics can lead to a poor accuracy of the predicted loads, and the mode acceleration method can be used to solve this problem. The present paper describes the advantages obtained using the mode acceleration method for load recovery and presents a procedure for the correction of aerodynamic forces using tabulated aerodynamic coefficients, showing their effect on the gust loads.